The possibility of language : a discussion of the nature of language, with implications for human and machine translation - Melby, Alan K. (Benjamins translation library ;, 1995)
This book is about the limits of machine translation. It is widely recognized that machine translation systems do much better on domain-specific controlled-language texts (domain texts for short) than on dynamic general-language texts (general texts for short). The authors explore this general - domain distinction and come to some uncommon conclusions about the nature of language. Domain language is claimed to be made possible by general language, while general language is claimed to be made possible by the ethical dimensions of relationships. Domain language is unharmed by the constraints of.